Stability of an Amorphous TiCuNi Alloy Subjected to High‐Pressure Torsion at Different Temperatures1. Issue 12 (11th September 2015) - Gunderov, Dmitry; Slesarenko, Viacheslav; Lukyanov, Alexander; Churakova, Anna; Boltynjuk, Evgeniy; Pushin, Vladinir; Ubyivovk, Evgeniy; Shelyakov, Alexander; Valiev, Ruslan
Abstract : The amorphous melt‐spun (MS) Ti50 Ni25 Cu25 alloy is subjected to high‐pressure torsion (HPT) at temperatures of 20‐150 °C. The bright‐field (BF) TEM images of the alloy change as a result of HPT processing, the view of the bright‐field image depends on the temperature of HPT processing. HPT processing leads to a decrease in the energy of structural relaxation during heating up to 400 °C, in comparison with the initial MS ribbons. The temperature of crystallization of the MS Ti50 Ni25 Cu25 alloy decreases after HPT processing by 40–20 °C (depends on the temperature of HPT processing). In the MS Ti50 Ni25 Cu25 alloy, HPT processing and subsequent annealing produces noticeably finer grains than annealing at 450 °C of the initial MS alloy. Consequently, HPT processing alters the crystallization kinetics of the MS Ti50 Ni25 Cu25 alloy. Abstract : In the melt‐spun (MS) Ti50Ni25Cu25 amorphous alloy after HPT at T = 150 °C, dark "clusters" (size ≈40 nm) separated by thin brighter interfaces are visible in the bright‐field TEM image, which may be a result of redistribution of free volume. HPT leads to a decrease in the energy of structural relaxation and alters the crystallization kinetics.